Statistically informed upscaling of damage evolution in brittle materials. (August 2019) - Vaughn, N.; Kononov, A.; Moore, B.; Rougier, E.; Viswanathan, H.; Hunter, A.
Highlights: Micro-cracks degrade the strength of brittle solids, impacting material response. On the continuum-scale this behavior must be homogenized due to computational cost. A workflow to scale micro-crack coalescence and growth behavior upwards is proposed. This model degrades elastic moduli with crack length and orientation statistics. Generated stress-strain curves show good comparison to experimental results. Abstract: The presence and growth of micro-cracks degrade the strength of brittle solids, greatly impacting the overall material response. Hence, the evolution of these micro-cracks must be accounted for in models describing the relationship between stress and strain so that accurate predictions of material failure can be made. The evolution of individual cracks and crack networks can be simulated with high-fidelity microscale models utilizing highly resolved meshes that can be computationally expensive to a point in which it limits the simulation scale. Hence, for many engineering applications that require simulations of large components, continuum-scale models, which cannot explicitly resolve individual cracks and thus lose important physical information, are required. In this work, we bridge these two scales by developing and implementing a continuum-scale effective moduli constitutive model that is informed by crack statistics generated from a high-fidelity model resolved using a finite-discrete element method (FDEM) implementation. Using statistical information describing the evolution of crack lengths and orientations, this model can capture the effects of brittle damage evolution without the need to resolve individual cracks. We have successfully captured the stress-strain behavior of the high-fidelity simulations using the statistics-based constitutive model shown through direct comparison of stress-strain curves. The curves match within error bars present in the strain-softening portions of the stress-strain curve of the high-fidelity results due to the statistical variation of the initial pre-existing crack network. The stress-strain curves are also compared to experimental results for similar loading conditions and show good qualitative agreement.